Students’ Academic Resilience Profiles based on Gender and Cohort - Latif, Suciani; Amirullah, Muhammad (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study examined the differences in the students’ academic resilience based on gender and cohort. Participants were students of Department of Educational Psychology and Guidance, Faculty of Education, Universitas Negeri Makassar in the academic years of 2013, 2014, and 2015. They were comprised of 103 students, 77 females and 26 males. The instrument in this study was Academic Resilience Scale (ARS) adopted and modified from Martin and Marsh. Data were analyzed through Mann-Whitney statistical of non-parametric tests in order to measure the academic resilience level of gender difference and Kruskal Wallis to measure academic resilience of cohort difference. Results revealed that there was no difference in academic resilience between female and male students. It was also found that there is a significant difference in academic resilience among the students in the academic years of 2013, 2014 and 2015. Discussion, limitation, and recommendation were also provided in this study.